Parenchymal‐sparing versus extended hepatectomy for colorectal liver metastases: A systematic review and meta‐analysis - Gang Deng; Hui Li; Gui‐qing Jia; Dan Fang; You‐yin Tang; Jie Xie; Ke‐fei Chen; Zhe‐yu Chen (Cancer Medicine, 2019)
Abstract Aims To assess the safety and efficacy of parenchymal‐sparing hepatectomy (PSH) as a treatment of colorectal liver metastases (CLM). Methods A comprehensive medical literature search was performed. Perioperative and long‐term survival outcomes were pooled. Subgroup analysis and meta‐regression analysis were performed to identify potential sources of heterogeneity. Results A total of 18 studies comprising 7081 CLM patients were eligible for this study. The PSH was performed on 3974 (56.1%) patients. We found that the OS (overall survival; hazard ratio [HR] = 1.01, 95% confidence interval [CI]: 0.94‐1.08) and RFS (recurrence‐free survival; HR = 1.00, 95% CI: 0.94‐1.07) were comparable between non‐PSH and PSH group. The perioperative outcomes were better in PSH than in non‐PSH group. Non‐PSH group was significantly associated with longer operative time (standard mean difference [SMD] = 1.17, 95% CI: 0.33‐2.00), increased estimated blood loss (SMD = 1.36, 95% CI: 0.64‐2.07), higher intraoperative transfusion rate (risk ratio [RR] = 2.27, 95% CI: 1.60‐3.23), and more postoperative complications (RR = 1.39, 95% CI: 1.16‐1.66). Meta‐regression analyses revealed that no variable influenced the association between surgical types and the survival outcomes. Conclusions This study shows that PSH is associated with better perioperative outcomes without compromising oncological outcomes. Given the increasing incidence of hepatic parenchyma, the PSH treatment offers a greater opportunity of repeat resection for intrahepatic recurrent tumors. It should be considered as an effective surgical approach for CLM.